2014
DOI: 10.1007/s10151-014-1219-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhoidal dearterialization with mucopexy versus hemorrhoidectomy: 3-year follow-up assessment of a randomized controlled trial

Abstract: Background A randomized controlled trial showed that patients with grade III or IV internal hemorrhoids had similar symptomatic relief of symptoms up to 3 months following dearterialization with mucopexy or hemorrhoidectomy albeit with less postoperative pain after the former. This study aimed to compare hemorrhoidal recurrence and chronic complications at 3-year follow-up.MethodsThis study was carried out on 40 patients with grade III or IV internal hemorrhoids previously enrolled to a randomized trial compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 16 publications
4
23
1
Order By: Relevance
“…Because our approach is not far from DG‐HAL, the fact that we find positive clinical results is encouraging . Furthermore, previous studies of embolization to treat acute bleeding have demonstrated efficacy and an absence of ischaemic complications for the use of this technique to treat life‐threatening rectal bleeding of various origins , as confirmed by the preliminary experience of our group with haemorrhoidal bleeding .…”
Section: Discussionsupporting
confidence: 63%
“…Because our approach is not far from DG‐HAL, the fact that we find positive clinical results is encouraging . Furthermore, previous studies of embolization to treat acute bleeding have demonstrated efficacy and an absence of ischaemic complications for the use of this technique to treat life‐threatening rectal bleeding of various origins , as confirmed by the preliminary experience of our group with haemorrhoidal bleeding .…”
Section: Discussionsupporting
confidence: 63%
“…According to literature sources 25 infection occurs in 5%-15% of patients, and relapse in 5%-30% 16,17,24,25,26 . Not a single case of urinary retention and no need to set a urinary catheter were registered in comparison to some literature data showing 0%-16% of cases with urinary retention and catheterization 21,27 . Average hospitalizations was 2.1 days in case of the MM method and 1 day after the LHP.…”
Section: Discussionmentioning
confidence: 72%
“…We chose to assess recurrence at 12 months because published data suggest that most HAL and RBL recurrences occur within 1 year. 26 Several studies have shown that using HAL for higher-grade haemorrhoids or significant prolapse adversely affects the recurrence rate; 19,37,41,66,67 they also conclude that HAL is perhaps most effective for grade II and early grade III disease. We therefore limited our trial to this most clinically relevant patient population.…”
Section: Main Findingsmentioning
confidence: 99%
“…The substantial data concerning effectiveness include four systematic reviews, 5,19-21 11 randomised controlled trials (RCTs), [22][23][24][25][26][27][28][29][30][31][32] seven non-randomised trials [33][34][35][36][37][38][39] and > 60 case series. An overview has been carried out by the National Institute for Health and Clinical Excellence (NICE), which concludes that current evidence shows it to be a safe alternative to OH or SH; 40 this is summarised below.…”
Section: Introductionmentioning
confidence: 99%